Mengklaim Ruang Publik: Analisis Awal Mengenai Non-gerakan Perempuan Aceh di Warung Kopi di Aceh - Hasbi, Baiquni (Saree: Research in Gender Studies, 2023)
This article discusses the significant role of Acehnese women in reshaping and claiming public spaces, with a specific focus on their participation in coffee shops as a case study. Employing a qualitative approach, the research analyzes the impact of disasters, the narratives of Acehnese recovery, and the influence of cultural values, as well as political and economic factors, on the women's movement in Aceh. Data collection involved literature review and document analysis. This initial analysis applies the concept of social non-gerakan to reveal how Acehnese women, without being driven by consistent ideologies or leadership, have influenced the transformation of public spaces in post-disaster Aceh. Despite facing criticism and regulations, the courage of Acehnese women in asserting their presence in public spaces has led to significant social changes in Aceh. This study highlights the importance of understanding the role of women in the transformation of public spaces and its implications for gender inclusivity in Acehnese society. Abstrak Artikel ini membahas peran penting perempuan Aceh dalam mengubah dan mengklaim ruang publik, dengan fokus pada partisipasi mereka di warung kopi sebagai studi kasus. Penelitian ini menggunakan pendekatan kualitatif untuk menganalisis dampak bencana, narasi perbaikan Aceh, dan pengaruh nilai-nilai budaya serta faktor-faktor politik dan ekonomi terhadap gerakan perempuan Aceh. Data dikumpulkan melalui penelitian literatur, dan analisis dokumen. Analisis awal ini mengaplikasikan konsep sosial non-gerakan untuk mengungkapkan bagaimana perempuan Aceh, tanpa didorong oleh ideologi atau kepemimpinan yang konsisten, telah mempengaruhi transformasi ruang publik di Aceh pasca-bencana. Meskipun menghadapi kritik dan regulasi, keberanian perempuan Aceh dalam mempertahankan kehadiran mereka di ruang publik telah memunculkan perubahan sosial yang signifikan di Aceh. Penelitian ini menggambarkan pentingnya memahami peran perempuan dalam transformasi ruang publik serta implikasinya terhadap inklusivitas gender dalam masyarakat Aceh